Utilization of the Canva application on the Belajar.Id site as a learning media at SMK Bina Nusa Mandiri Jakarta - Putri, Indira; Jumardi, Jumardi (Universitas Negeri Yogyakarta, 2023)
This study aims to discover the use of the Canva Education Application as a learning medium accessed through web learning. id for teachers at SMK Bina Nusa Mandiri Jakarta. This research is a type of qualitative research with a literature study approach. Literature study qualitative research consists of 4 stages: making interview instruments, looking for reading material, recording, and analyzing research material obtained. The results of interviews conducted with teachers at SMK Bina Nusa Mandiri show that the Canva Education application is handy because it can help teachers create engaging learning media for students. The Canva Education application has various features teachers can use to create learning media, such as PPTs, learning videos, infographics, etc. The research results show that the Education Canva Application facilitated by the Ministry of Education and Culture allows teachers at Bina N`usa Mandiri Vocational School to create learning media using only the learn quickly. Id website and can already get the Canva Application for free. The meaning of using the Canva application on learning.id website for history teachers at Bina Nusa Mandiri Vocational School is to be an exciting learning medium because history lessons are famous for lessons that only focus on books. The Canva application learning media has various templates and can also be used to make history-learning videos look interesting. The Canva App can vary in history lessons.